SISTEM INFORMASI GEOGRAFIS UNTUK PEMETAAN LOKASI MASJID DAN MEUNASAH DI KOTA LHOKSEUMAWE MENGGUNAKAN ALGORITMA HAVERSINE BERBASIS WEBSITE: GEOGRAPHIC INFORMATION SYSTEM FOR MAPPING THE LOCATION OF MOSQUES AND MEUNASAH IN LHOKSEUMAWE CITY USING THE WEBSITE-BASED HAVERSINE ALGORITHM - Agus Prayoga; Fadlisyah Fadlisyah; Hafizh Al kautsar Aidilof (LPPM Universitas Abdurrab, 2025)
This research aims to develop a web-based Geographic Information System (GIS) that maps the location of mosques and meunasah in Lhokseumawe City, and uses the Haversine Algorithm to calculate the closest distance between users and places of worship. The main purpose of this system is to provide fast, accurate, and efficient information, especially for newcomers or residents in finding the nearest place of worship. The method used is the waterfall system development model, with system design using the Unified Modeling Language (UML) to visualize the workflow and data structure. Data is obtained through interviews with mosque administrators and the community, as well as taking coordinates using a GPS device. The test results show that the Haversine Algorithm can calculate the distance accurately and find the location of the nearest mosque or meunasah based on the user's position. However, this system has limitations because distance calculations only consider straight lines between points (geodesic), without taking into account the actual route of the road. This research concludes that a web-based GIS that integrates the Haversine Algorithm provides real-time distance information, makes it easier for people to find the nearest place of worship, and increases the accessibility of information and participation in religious activities in Lhokseumawe City.